Pemanfaatan Bahan Alam untuk Pembuatan Foot Care di SMK Batik 1 Surakarta: Use of Natural Materials for Making Foot Care at Batik 1 Vocational School Surakarta - Prastiwi, Rini; Dewanti, Ema; Ladeska, Vera; Sunaryo, Hadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Improving entrepreneurship skills is very important in the current state of the COVID-19 pandemic. The number of layoffs carried out by the industrial world is one of the reasons for the high number of layoffs now. Entrepreneurial skills are an important part of educating school children from the start so that after graduation they are expected to open up job opportunities for themselves and others. Vocational High School (SMK) is now one of the schools that can produce skilled and innovative personnel. One of the private vocational schools in Surakarta that is trying to do that is SMK BATIK 1. The UHAMKA FFS Service Team provides training and guidance on the pharmacy expertise program to make foot care preparations, in the form of foot sanitizer and foot lotion. Preparations made from natural ingredients lemongrass extract, ginger extract, and coffee extract. Activities include lectures and workshops. Activities provide benefits in the form of increasing the soft skills and hard skills of students in utilizing natural materials in dosage forms which will increase the selling value.